Teologi Kitab Kisah Para Rasul dan Sumbangannya dalam Pemahaman Sejarah Keselamatan - Paulus Kunto Baskoro (Jurnal Teologi (JUTEOLOG), 2020)
Salvation is a mighty work that Jesus did for all mankind. This is a serious problem for humans, namely the settlement of sins, which can also be explored from the Book of Acts. Yet many people feel that the Book of Acts is merely church history and does not have a strong contribution to the history of salvation. Based on the above facts, it is necessary to present the theologies in the Book of Acts and their contribution to the work of salvation for mankind. And the Book of Acts is also the starting point of a movement for God's church which is the basis of the gospel message to all people. Through the theological concepts that appear in the Book of Acts of the Apostles will be implemented for believers and the church today, so as to become a strong foundation for the movement of God's church in the work of the history of salvation until the end of time.